2016
DOI: 10.24953/turkjped.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Increased mean platelet volume in children with sepsis as a predictor of mortality

Abstract: Our aim is to investigate the correlation between the mean platelet volume (MPV) levels and platelet counts of the septic children with 28-day mortality risk. MPV at admission (MPV < sub > adm < /sub > ), MPV at 72 < sup > nd < /sup > hour (MPV < sub > 72h < /sub > ) and the difference between these two parameters (ΔMPV < sub > 72h-adm < /sub > ) and platelet counts were recorded retrospectively. The control group consisted of 100 healthy children matched for age, gender, and ethnicity. One hundred eighty six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
1
12
1
Order By: Relevance
“…Our meta-analysis provides strong support for greater organ dysfunction in nonsurvivors compared with survivors as shown by the pooled estimates for renal dysfunction ( 50 , 64 , 67 , 70 ), multi-organ dysfunction (MODS) ( 23 , 33 , 41 , 50 , 69 , 70 , 93 , 94 ), number of organ dysfunctions ( 28 , 40 , 64 , 83 ), PEdiatric Logistic Organ Dysfunction (PELOD) score ( 23 , 28 , 40 , 44 , 50 , 53 , 55 , 60 , 65 , 72 , 85 ), and PELOD-2 ( 85 , 86 , 95 ). Our meta-analysis also provides strong support for greater illness severity in nonsurvivors compared with survivors as shown by the pooled estimates pediatric Sequential (Sepsis-related) Organ Failure Assessment (pSOFA) ( 50 , 58 , 70 , 95 ) and Sequential (Sepsis-related) Organ Failure Assessment (SOFA) ( 85 , 86 , 95 ), PRISM ( 32 , 43 , 51 , 53 , 55 , 60 62 , 64 , 68 , 70 72 , 75 , 77 , 81 , 84 , 85 , 88 ), Pediatric Index of Mortality (PIM)-2 ( 79 , 85 ), and PIM-3 ( 23 , 61 , 65 , 85 ) (Supplementary Fig. 7,…”
Section: Resultssupporting
confidence: 59%
“…Our meta-analysis provides strong support for greater organ dysfunction in nonsurvivors compared with survivors as shown by the pooled estimates for renal dysfunction ( 50 , 64 , 67 , 70 ), multi-organ dysfunction (MODS) ( 23 , 33 , 41 , 50 , 69 , 70 , 93 , 94 ), number of organ dysfunctions ( 28 , 40 , 64 , 83 ), PEdiatric Logistic Organ Dysfunction (PELOD) score ( 23 , 28 , 40 , 44 , 50 , 53 , 55 , 60 , 65 , 72 , 85 ), and PELOD-2 ( 85 , 86 , 95 ). Our meta-analysis also provides strong support for greater illness severity in nonsurvivors compared with survivors as shown by the pooled estimates pediatric Sequential (Sepsis-related) Organ Failure Assessment (pSOFA) ( 50 , 58 , 70 , 95 ) and Sequential (Sepsis-related) Organ Failure Assessment (SOFA) ( 85 , 86 , 95 ), PRISM ( 32 , 43 , 51 , 53 , 55 , 60 62 , 64 , 68 , 70 72 , 75 , 77 , 81 , 84 , 85 , 88 ), Pediatric Index of Mortality (PIM)-2 ( 79 , 85 ), and PIM-3 ( 23 , 61 , 65 , 85 ) (Supplementary Fig. 7,…”
Section: Resultssupporting
confidence: 59%
“…According to Işgüder et al (13) non survivors showed a considerably lower platelet count than survivors (p-value 0.002). At logistic regression analysis, platelet count (OR 7.3) demonstrated a significant impact on the probability of 28-day mortality risk.…”
Section: Discussionmentioning
confidence: 94%
“…In agreement, Kim et al [20] reported that non-survivors exhibited significant higher baseline and day 3 MPV values. Also, İşgüder et al [33] showed that non-survivors had significant high MPV on admission and 72 h later. MPV in both groups was higher on day 3 than admission; this result is in concordance with study done by Kim et al in which MPV was higher at 72 h than baseline in both non-survivors and survivors [20].…”
Section: Discussionmentioning
confidence: 99%